HUBUNGAN ANTARA PENGETAHUAN TENTANG PENYAKIT DAN KOMPLIKASI PADA PENDERITA DIABETES MELITUS DENGAN TINDAKAN MENGONTROL KADAR GULA DARAH DI WILAYAH KERJA PUSKESMAS I GATAK SUKOHARJO - Nina Rahmadliyani; Abi Muhlisin (Universitas Muhammadiyah Surakarta, 2008)
The increasing of prevalence of diabetes mellitus sickness in Indonesia reached five million in 1995 with the rate of increasing 230.000 annually so that in 2005 it was estimated that diabetes mellitus sickness would have reached 17 million people or 8.6% of the total of the world population (October 2005). The causes of this disease is the lack of understanding about diabetes mellitus disease. The increasing of life, diet, fatness, and the way modern of life. According to American Diabetes Association (ADA) 2003, diabetes mellitus is a group of metabolic disease with hyperglycemia characteristic which takes place because of indifferent insulin sucrose, insulin work or both of them. Hyperglycemia chronic in diabetes deals with the damages for long time, malfunction, and failure of several organs of the body, especially eyes, kidney, nerves, heart, and blood vessel. Research methodology which is used here is Descriptive methodology with analysis data technique which use correlation analysis Spearman rank. From the data analysis it finds arithmetic R = 0,508 if it is consulted with R table Spearman RHO to significant degree 5% and N = 42 got table R 0,304 and significant degree 1% got from the result 0,393, so it can be concluded that there is a significant correlation between knowledge of disease and the complication to diabetes mellitus patient which check their degree of glucose in the blood in Puskesmas I Gatak Sukoharjo.